2018
DOI: 10.1186/s41235-018-0123-6
|View full text |Cite
|
Sign up to set email alerts
|

Inversion effects in the expert classification of mammograms and faces

Abstract: A hallmark of a perceptual expert is the ability to detect and categorize stimuli in their domain of expertise after brief exposure. For example, expert radiologists can differentiate between “abnormal” and “normal” mammograms after a 250 ms exposure. It has been speculated that rapid detection depends on a global analysis referred to as holistic perception. Holistic processing in radiology seems similar to holistic perception in which a stimulus like a face is perceived as an integrated whole, not in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…Another popular model posits that initial global processing (consisting of bottom–up “global image statistics” like average orientation and average size of objects) signals if there is an abnormality (establishing its likelihood) without providing location information or constraining the subsequent serial search. The searcher can then change their strategy to a slower, more complete search for the abnormality (Evans et al, 2010, 2016; Drew et al, 2013a; Chin et al, 2018) (Figure 3).…”
Section: Holistic ‘Gist’ Processing Theorymentioning
confidence: 99%
“…Another popular model posits that initial global processing (consisting of bottom–up “global image statistics” like average orientation and average size of objects) signals if there is an abnormality (establishing its likelihood) without providing location information or constraining the subsequent serial search. The searcher can then change their strategy to a slower, more complete search for the abnormality (Evans et al, 2010, 2016; Drew et al, 2013a; Chin et al, 2018) (Figure 3).…”
Section: Holistic ‘Gist’ Processing Theorymentioning
confidence: 99%
“…Because we do not have a precise measurement of the size of the tumor relative to the cutout, even the small cutout may have included some surrounding tissues, accounting for why performance was moderate but above chance. Although local contrast but not the larger background was important in our study, it remains possible that more extensive training may lead to greater reliance on the entire image (Chin et al, 2018). The forced-choice training procedure, with normal and abnormal images presented side by side, does not resemble radiological diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…As noted earlier, radiologists can rapidly extract the global image statistics to render an initial decision on whether a mammogram may be cancerous (Evans et al, 2016;Evans, Georgian-Smith, Tambouret, Birdwell, & Wolfe, 2013;Nodine et al, 1999). Additionally, presenting mammograms in an inverted orientation impairs radiologists' performance, suggesting that breast cancer detection is holistic (Chin, Evans, Wolfe, Bowen, & Tanaka, 2018). If perceptual learning of chest radiographs also involves the learning of global image statistics, then performance should decline when just the tumor cutout or just the background is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, radiologists are a limited resource [27], with a small amount of time available to dedicate to the experiment. For this reason, the number of qualified radiologists has been around ten individuals in most recent studies, e.g., [4,31,32,36,40]. We acknowledge that one cannot necessarily apply conclusions made in one study to the entire population.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive training leads to the increased tuning of visual perception [28] and changes in search strategy which radiologists implement during image reading [29]. Most previous studies have demonstrated the strong top-down influence of expertise when comparing the performance of radiologists and non-radiologists viewing medical images [29][30][31][32][33]. In addition, the tracking of brain activity revealed significant differences among radiologists and non-radiologists, not only for radiology-related images, but also for control images [34].…”
Section: Ergonomic Evaluation Of Visualization Methodsmentioning
confidence: 98%